A bifurcação da corrente do Brasil no embaiamento de Tubarão e seu papel na formação de vórtices ciclônicos - Servino, Ricardo Nogueira (2014)
The transition region from the east to the southeast Brazilian coast, between 19°S and 21°S, shows remarkable geomorphological features that characterizes a complex shelf-break line. The Abrolhos Banks and the Vitória-Trindade Ridge’s (VTR) seamounts are irregularities that promote influences on the system of western boundary currents in this region, specially to the Brazil Current (BC), inducing its meandering and the developing of eddies locally. Confined by these structures around it, the Tubarão Bight (TB) is a region in front of Vitória (20.3°S; 40.3°W) that shelters cyclonic eddies which formation was investigated in this work as influenced by a bifurcation of the BC in this site. The bifurcation of a geostrophic current is a geophysical process of interaction between a jet and a continental boundary that results in the formation of two secondary jets – one in each direction – and that can be responsible for the developing of eddies inside partially confined oceanic basins (e.g Alboran Sea and Sea of Japan). The occurrence of this process was found inside the TB following the impinging of the BC on its continental slope, identified based on numerical modelling results derived from a high-resolution and refined topography simulation. To the extent of our knowledge, this is the first description of such process in this region. This work’s findings suggest that the secondary jet deflected to the TB’s interior is necessary to the developing and maintenance of two kinds of eddies with different size, duration and date of occurrence. These eddies’ characteristics and the bifurcation’s itself were significantly linked to the flowing pattern of the BC through the VTR’s seamounts.